Basal cisternostomy – Is it a panacea for traumatic brain swelling? - Cherian, I (Journal of College of Medical Sciences-Nepal, 2012)
The evolution of modern neurosurgical techniques in traumatic brain injury has been ongoing for the last two centuries. However it has always been a challenge to obtain an effective clinical outcome, especially those following severe traumatic brain injuries. Other than the well established procedures for acute and/ or chronic subdural hematomas and depressed skull fractures, newer avenues for development of surgical techniques where indicted have been minimal. Practical scenario in trauma neurosurgery comes with multiple challenges and limitations. In an emergency setup, primary management of traumatic brain injuries fall upon the on-duty resident or medical officer in training. Due to the emergent nature of the condition and time being an important variable, the experience of the operating surgeon as well as the severity of the injury become an important contributing factor in the disease prognosis. Based on clinical experience and observation of acute neurosurgical service in tertiary medical center in a developing country, a novel technique in the management of trauma neurosurgery have been elucidated in the current study. The study proposes to apply the principles of microvascular surgery and skull base surgery in selected cases of severe traumatic brain injuries. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-1, 1-6 DOI: http://dx.doi.org/10.3126/jcmsn.v8i1.6818